2002
DOI: 10.1016/s0006-3495(02)75522-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Ultrasound Backscattering by Red Cell Aggregates:Effect of Shear Rate and Anisotropy

Abstract: Tissue characterization using ultrasound (US) scattering allows extraction of relevant cellular biophysical information noninvasively. Characterization of the level of red blood cell (RBC) aggregation is one of the proposed application. In the current paper, it is hypothesized that the microstructure of the RBCs is a main determinant of the US backscattered power. A simulation model was developed to study the effect of various RBC configurations on the backscattered power. It is an iterative dynamical model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…The mathematical model of blood flow and pressure has been presented in [16,17]. Adequate cellular biophysical data can be extracted without invasion due to ultrasound scattering, which allows tissue characterization and determination of red blood cell aggregation [18,19]. Some years ago, power ultrasound was considered too expensive for water treatment in the industry [20].…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical model of blood flow and pressure has been presented in [16,17]. Adequate cellular biophysical data can be extracted without invasion due to ultrasound scattering, which allows tissue characterization and determination of red blood cell aggregation [18,19]. Some years ago, power ultrasound was considered too expensive for water treatment in the industry [20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro studies have shown that aggregation of blood increases as shear rate decreases. Aggregation also depends on hematocrit and the concentration of macromolecules in the plasma or suspending medium (7,10,15,16,19,25,32). However, the circumstances in which aggregation occurs in vivo and its possible importance in circulatory function are not well understood.…”
mentioning
confidence: 99%
“…aggregating red blood cell distributions) by introducing the frequency dependent structure factor, and called the Structure Factor model (SFM). 15,16 The SFM sums the contributions from individual cells and models the cellular interaction by a statistical mechanics structure factor, which is defined as the Fourier transform of the spatial distribution of the cells. 15,16 Note that the low frequency limit of the structure factor is by definition the packing factor used under Rayleigh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The SFM sums the contributions from individual cells and models the cellular interaction by a statistical mechanics structure factor, which is defined as the Fourier transform of the spatial distribution of the cells. 15,16 Note that the low frequency limit of the structure factor is by definition the packing factor used under Rayleigh conditions. 13 Until quite recently, the PM and SFM were only used for blood characterization purposes, but…”
Section: Introductionmentioning
confidence: 99%